Targeting Tumor Physical Microenvironment for Improved Radiotherapy. Issue 11 (18th September 2022) - Wang, Jin; Han, Yulong; Li, Yuan; Zhang, Fengping; Cai, Mengjiao; Zhang, Xinyue; Chen, Jie; Ji, Chao; Ma, Jinlu; Xu, Feng
Abstract: Radiotherapy has led to important clinical advances; existing cancer radiotherapy resistance is one remaining major challenge. Recently, biophysical cues in the tumor microenvironment (TME) have been regarded as the new hallmarks of cancer, playing pivotal roles in various cancer behaviors and treatment responses, including radiotherapy resistance. With recent advances in micro/nanotechnologies and functional biomaterials, radiotherapy exerts great influence on biophysical cues in TME, which, in turn, significantly affect the response to radiotherapy. Besides, various strategies have emerged that target biophysical cues in TME, to potentially enhance radiotherapy efficacy. Therefore, this paper reviews the four biophysical cues (i.e., extracellular matrix (ECM) microarchitecture, ECM stiffness, interstitial fluid pressure, and solid stress) that may play important roles in radiotherapy resistance, their possible mechanisms for inducing it, and their change after radiotherapy. The emerging therapeutic strategies targeting the biophysical microenvironment, to explore the mechanism of radiotherapy resistance and develop effective strategies to revert it for improved treatment efficacy are further summarized. Abstract : Radiotherapy and biophysical cues in the tumor microenvironment (TME) interact with each other. Radiotherapy remodels TME with decreased extracellular matrix (ECM) stiffness, solid stress, interstitial fluid pressure (IFP), and organized microarchitecture. Meanwhile, the elevation of ECM stiffness, solid stress, IFP, and disrupted microarchitecture lead to radioresistance. Mechanotherapy targets the biophysical cues in the tumor physical microenvironment to improve radiotherapy efficacy.